The 53rd Open Seminar on Acoustics OSA 06 - Wiciak, Jerzy; Uchryński, Andrzej (Archives of Acoustics, 2006)
Zakopane, 11-15 September, 2006 The conference is organized by the Division of the Polish Acoustical Society in Kraków and Department of Mechanics and Vibroacoustics at the Faculty of Mechanical Engineering and Robotics, AGH University of Science and Technology. he conference will be devoted to different aspects of theoretical and experimental research in the field of acoustics. Eight invited papers will be delivered by the following speakers: Dr hab. inż. Andrzej Dobrucki, Wrocław University of Technology, Wrocław; Prof dr hab. inż. Zbigniew Engel, AGH University of Science and Technology, Kraków; Dr hab. inż. Grażyna Grelowska, Naval University of Gdynia, Gdynia; Prof. dr hab. inż. Jan Kaźmierczak, Silesian University of Technology, Gliwice; Dr hab. Piotr Kleczkowski, AGH University of Science and Technology, Kraków; Prof. dr. hab. inż. Tadeusz Powałowski, Institute of Fundamental Technological Research, Warszawa; Dr hab. Anna Preiss, Adam Mickiewicz University, Poznań; Dr hab. inż. Stefan Weyna, Szczecin University of Technology, Szczecin. The 11 contributed sessions are planed. There are 131 contributing papers which will be presented during the meeting.